Leveraging Commercial Cubesat Constellations for Auroral Science: A Case Study. Issue 5 (27th May 2019) - Parham, J. Brent; Beukelaers, Vincent; Leung, Lawrence; Mason, James; Walsh, Brian; Semeter, Joshua
Abstract: Magnetometers deployed on the largest satellite constellation to date are leveraged as a space‐based sensor network to study space‐time variability in auroral field‐aligned currents (FACs). The cubesat constellation of Planet Labs Inc. consists of nearly 200 satellites in two polar Sun‐synchronous orbits, with median spacecraft separations on the order of 375 km, and some occasions of opportunity providing much closer spacing. Each spacecraft contains a magnetoinductive magnetometer, able to sample the ambient magnetic field at 0.1 to 10 Hz with <200‐nT sensitivity. In this study, seven satellites from the Planet constellation were used to investigate space‐time variations in FACs over an active auroral display during a 10‐min interval. The aurora occurred during the early recovery phase of a geomagnetic storm and was characterized by large‐scale vortical motions and embedded rayed structure. Clear signatures of the large‐scale auroral current system were detected by the orbital magnetometers. Estimation of FAC patterns was carried out using three different methods. The results suggest a high degree of spatial and temporal variability during the 10‐min interval. The location of upward and downward current channels relative to the aurora was consistent with theoretical expectations, but current densities were not well correlated with visible features in the available imagery, suggesting unresolved small‐scale structure not captured by the collaborative observations. Advantages, limitations, and caveats in using opportunistic networks of low‐quality space‐based magnetometers to study dynamic auroral phenomena are discussed. Key Points: Dense satellite constellations developed by the commercial sector can be leveraged as opportunistic geospace observatories The magnetometers on the 200 element constellation of Planet Labs is used to study space‐time variability in auroral field‐aligned currents Results using seven satellites crossing an auroral arc reveal a remarkable degree of variability over a 10‐min interval